Gupte/Bull shoulder brace - Gupte,CM; Bull,AMJ (2008)
A joint brace, for example a shoulder brace, includes one or more straps (2) attached across the joint in question such that rotation of the joint is controlled. The joint brace includes a flexion limiting brace (6) worn, for the shoulder example, at the elbow. The flexion limiting brace provides a point of attachment (60) for the strap or straps.